Methodical basis and administrative and managerial bases for improving the operational and production system and organizational structure of a development company - Chernyshev, D.; Tugay, А.; Pokolenko, V.; Gorbach, M.; Malykhin, M.; Skakyn, E. (Ways to Improve Construction Efficiency, 2019)
The article analyzes and improves scientific methodical approaches and applied tools for choosing the options for organizing a construction project throughout the investment cycle, including design, design, preparation and construction. The content and structure of the stages of the building development project as a specific resource-time environment has been redesigned, integrating the organizational-technological capabilities and economic interests of its leading non-qualified participants into the outdated scientific and methodological basis of construction preparation.